Prevalence and determinants of late first antenatal care initiation in western Ethiopia: findings from a multi-centered cross-sectional study - Amsalu, Atitegeb Alebachew; Yalew, Alemayehu Worku; Zemlak, Awgichew Kifle (Frontiers in Reproductive Health, 2025)
BackgroundLate initiation of antenatal care (ANC) continues to be a significant public health issue in sub-Saharan African countries, including Ethiopia. However, despite the high prevalence of late ANC initiation in Ethiopia, only a few studies have been conducted, particularly in developing regions, such as Bebishangul-Gumez. Therefore, this study aims to assess the prevalence of late initiation of the first ANC and associated factors among pregnant women in Western Ethiopia, 2023MethodsA facility-based cross-sectional study was conducted in Western Ethiopia from March 28, 2023 to April 30, 2023. We employed a systematic random sampling technique to select 427 participants. Data were collected using an electronic capture technique with open data kit (ODK), then, transported to XLS and exported to Stata version 17 software for analyses. Bivariate analysis was performed at significance level of p-value < 0.25 to select candidate variables for multivariable analysis. In the final model, factors with a p-value ≤ 0.05 were considered significantly associated with late initiation of ANC.ResultsA total of 414 pregnant women participated, yielding a response rate of 96.9%. The prevalence of late first ANC booking in this study was 56.8% (95% CI: 51.9, 61.5). Multivariable analysis revealed that being a housewives (AOR = 2.09, 95% CI 1.09, 4.01), having education status below secondary school (AOR = 3.5, 95% CI: 1.9, 6.1), having an unplanned pregnancy (AOR = 3.01, 95% CI 1.31, 6.90), lack of advise on when to start ANC (AOR = 1.74, 95% CI (1.09, 2.79), and attending ANC at hospital reduce the odds of late initiation of ANC (AOR = 0.41, 95% CI, 0.23, 0.72) were factors significantly associated with the late initiation of ANC.ConclusionThe prevalence of late initiation of ANC was found to be high in the study area. Educational status below secondary school, unplanned pregnancy, lack of advice on when to start ANC, housewives and attending ANC at hospital were factors found to be significantly associated with the late initiation of ANC. Therefore, policies should be developed to increase support for female education, maintain women's empowerment initiatives through economic changes, expand family planning programs to decrease unplanned pregnancies, and increase awareness in the early initiation of ANC.